1981
DOI: 10.1152/ajpgi.1981.241.2.g129
|View full text |Cite
|
Sign up to set email alerts
|

Human esophageal response to rapid swallowing: muscle refractory period or neural inhibition?

Abstract: The peristaltic response of the normal human esophagus to 10 repeated water swallows separated by varying time intervals (5, 10, 15, 20, and 30 s) between swallows was studied. Pressures measured during the shorter time intervals were of lower amplitude than those at 30-s swallowing intervals throughout the esophagus, with the distal esophagus showing the greatest effect. Frequency of peristalsis was decreased throughout the esophagus with rapid swallowing, especially distally at the 5- and 10-s time intervals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0
7

Year Published

1983
1983
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 0 publications
3
59
0
7
Order By: Relevance
“…This observation indicates that each new deglutition may inhibit the activity of the previous swal low. This phenomenon has been called 'deglutitive inhibi tion' [22][23][24][25], In addition to the effect of a second swallow on a previous swallow, the occurrence of a previous swal low can dramatically alter the nature of a subsequent swallow, decreasing its amplitude and at times rendering it nonperistaltic. This effect has been called 'refractori ness'.…”
Section: Discussionmentioning
confidence: 99%
“…This observation indicates that each new deglutition may inhibit the activity of the previous swal low. This phenomenon has been called 'deglutitive inhibi tion' [22][23][24][25], In addition to the effect of a second swallow on a previous swallow, the occurrence of a previous swal low can dramatically alter the nature of a subsequent swallow, decreasing its amplitude and at times rendering it nonperistaltic. This effect has been called 'refractori ness'.…”
Section: Discussionmentioning
confidence: 99%
“…Repetitive swallowing at short intervals, as occurs during drinking of liquids, produces an esophageal response characterized by quiescence until the last of the swallows, which is then followed by an esophageal contraction (6)(7)(8). Meyer et al (7) have also shown that two or more swallows taken in rapid succession may markedly influence the response to the preceding swallows.…”
Section: Introductionmentioning
confidence: 99%
“…It thereby inhibits contraction in the esophageal body, and relaxes the LES [12]. Under physiological circumstances, the last swallow is often followed by a vigorous peristaltic contraction and a post-swallow LES after-contraction [31]. Both maneuvers generally test the overall integrity of the esophageal neuromuscular control, because a normal response requires intact inhibitory and excitatory central and peripheral neural pathways along with sufficient muscle reserve to produce a vigorous peristaltic contraction with or after the final swallow.…”
Section: Provocation Testsmentioning
confidence: 99%